VLSI-SoC : new technology enabler : 27th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2019, Cusco, Peru, October 6-9, 2019, revised and extended selected papers /: 27th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2019, Cusco, Peru, October 6-9, 2019, revised and extended selected papers. (2020) - Unknown
No abstract available